2019
DOI: 10.1111/ppa.13035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of a Pyrenophora teres f. teres population over time in an Australian barley field as revealed by Diversity Arrays Technology markers

Abstract: Net form of net blotch caused by Pyrenophora teres f. teres (Ptt) is a major foliar disease of barley (Hordeum vulgare) worldwide. Knowledge of the evolution of Ptt pathogen populations is important for development of durable host‐plant resistance. This study was conducted to investigate changes in genetic structure of a Ptt population within a barley field during three cropping years. The susceptible barley cultivar Henley was inoculated with Ptt isolate NB050. Leaf samples were collected during the years 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…These genetic variations were driven by sexual reproduction, gene flow and transposable element invasion. More recently, Ptt population genetic studies using Diversity Arrays Technology (DArT) found rapid changes in population genetic structure under field conditions (Poudel et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…These genetic variations were driven by sexual reproduction, gene flow and transposable element invasion. More recently, Ptt population genetic studies using Diversity Arrays Technology (DArT) found rapid changes in population genetic structure under field conditions (Poudel et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The advanced DArT technology also identifies single nucleotide polymorphisms (SNPs) within sequences. This technology has been previously implemented for genetic population analysis of fungal species including P. teres (Martin et al 2020;Poudel et al 2019;Syme et al 2018).…”
mentioning
confidence: 99%
“…Association mapping requires high-throughput genotyping and sequencing methods to provide large numbers of markers. One such method, Diversity Arrays Technology sequence (DArTseq), has been developed for a number of fungal pathogens, including P. teres (Poudel et al 2019b;Sharma et al 2014;Syme et al 2018;Wittenberg et al 2009). DArTseq involves a combination of genomic complexity reduction methods and next generation sequencing, where the markers detect single-nucleotide polymorphisms (SNPs) and the presence/absence of fragments (Courtois et al 2013;Cruz et al 2013;Kilian et al 2012;Raman et al 2014).…”
mentioning
confidence: 99%